Analysis of Fuel Usage in Biogas Power Plant at PT. Berkat Sawit Sukamaju Palembang - Putra, Kurniawan; ., Rahmaniar; Dalimunthe, Muhammad Erpandi (Power Elektronik : Jurnal Orang Elektro, 2025)
PT Berkat Sawit Sukamaju is an oil palm processing plant with a capacity of 45 tonnes/hour which requires electrical energy in processing FFB into CPO, so far the energy used comes from diesel and steam power plants. However, problems arise when the price of industrial diesel as diesel fuel increases and the selling value of shells as biomass turbine fuel increases, therefore PT. Berkat Sawit Sukamaju built a biogas power plant with a capacity of 3x1 MW. Biogas power plant (PLTBg) is a power plant that is fuelled by methane gas from liquid waste / POME factory, but it is necessary to know the efficiency of the use of methane gas fuel used whether it is effective or not so that the energy produced can be optimal. This study was conducted to analyse the use of fuel in the biogas power plant at PT Berkat Sawit Sukamaju so that the efficiency of fuel use and the economic value of the company after the biogas plant operates can be known. Using the quantitative method, it can be seen that the fuel efficiency is 40.09% and PT. Berkat Sawit Sukamaju gets a profit of Rp. 295,760,320 / month from saving the use of shells and diesel.